2011
DOI: 10.1002/maco.200905426
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic protection of XL 52 steel under the influence of sulfate reducing bacteria

Abstract: The effect of sulfate reducing bacteria (SRB) upon the cathodic protection of XL 52 steel was determined, in order to identify if the potential value of À0.950 V versus copper/copper sulfate electrode is good enough to protect the metal surface. During the experiments, different operational parameters were monitored: hydrogen sulfide production, iron concentration, electrolyte alkalinity, microorganisms' population, as well as the metal surface damage. At the same time, the corrosion rate was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…To minimize the environmental toxicity and enhance the biocidal functionality of biocides against biofilms, natural biocides, such as amino acids and natural extracts, have been used together with traditional biocides to synergistically act on the MIC of SRB. Organic inhibitors have gained considerable attention in inhibiting MIC in recent years, but they face similar dilemmas to biocides on their inherent toxicity to the environment, high cost, and the difficulty in implementing them in open systems. Alternatively, cathodic protection has been proven to be less effective to resist the SRB adhesion and the initiation of localized corrosion caused by SRB . On the other hand, protective antifouling paints, which are formulated with toxic copper or organotin compounds, have been completely banned from usage in marine environments since 2008 due to their adverse effect on nontargeted creatures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the environmental toxicity and enhance the biocidal functionality of biocides against biofilms, natural biocides, such as amino acids and natural extracts, have been used together with traditional biocides to synergistically act on the MIC of SRB. Organic inhibitors have gained considerable attention in inhibiting MIC in recent years, but they face similar dilemmas to biocides on their inherent toxicity to the environment, high cost, and the difficulty in implementing them in open systems. Alternatively, cathodic protection has been proven to be less effective to resist the SRB adhesion and the initiation of localized corrosion caused by SRB . On the other hand, protective antifouling paints, which are formulated with toxic copper or organotin compounds, have been completely banned from usage in marine environments since 2008 due to their adverse effect on nontargeted creatures .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, cathodic protection has been proven to be less effective to resist the SRB adhesion and the initiation of localized corrosion caused by SRB. 31 On the other hand, protective antifouling paints, which are formulated with toxic copper or organotin compounds, have been completely banned from usage in marine environments since 2008 due to their adverse effect on nontargeted creatures. 32 Based on the fact that the initial bacterial attachment and biofilm formation are the first step in initiating MIC, in recent years considerable efforts have been devoted to the development of green polymeric coatings incorporated with antimicrobial moieties.…”
Section: Introductionmentioning
confidence: 99%
“…31 Despite high effectiveness in resisting biofouling and biocorrosion in marine environments, protective coatings, such as tributyltin (TBT)-based paints, have been completely phased out since 2008 due to their toxicity to nontargeted marine organisms. 32 On the other hand, the efficiency of cathodic protection has also been found to significantly decrease in an SRB-induced corrosion system, 33 since the high applied positional has no effect on the adhesion of anerobic bacteria and is unable to prevent the initiation of localized corrosion by SRB. 34 In view of the complex environmental, ecological, and economical impacts, an alternative effective approach to covalently immobilize antibacterial coatings on metal surface has been developed to inhibit biocorrosion induced by SRB in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In some standards such as NACE RP0169-02 and DNV-RP-B401-05, the minimum CP potential of −0.950 V (CSE) is recommended in steel pipes in the presence of microorganisms. Some researchers reported that the cathodic potential of −0.950 V (CSE) could not provide effective protection for steel pipelines [10] and some scholars even proposed that the CP potential of −1.35 V (CSE) achieved the ideal protection effect [11]. However, in some studies [12][13][14][15], the biofilm promoted hydrogen absorption in high-strength steel under the synergistic action of cathode polarization and SRB and greatly increased the The experimental solution was a near-neutral pH solution, NS4 solution composed of 0.137 g l −1 CaCl 2 , 0.122 g l −1 KCl, 0.131 g l −1 MgSO 4 •7H 2 O, and 0.483 g l −1 NaHCO 3 .…”
Section: Introductionmentioning
confidence: 99%